Study on the Deformation Mechanism of the Bottom Plate along the Empty Lane of Deep Mining and the Control Technology of the Bottom Drum. (13th September 2022) - Pang, Dongdong; Niu, Xingang; He, Kai; Li, Chuanming; Pang, Dawei; Hu, Tao; Chen, Zhongqi; Luo, Xiaolong
Abstract : Aiming at the problem of the deformation of the roadway floor plate during the laneway during the retention period, the mechanical model of the roadway floor is established, and the deformation characteristics of the roadway floor and the change law of the bottom drum are studied and analyzed through theoretical calculation and calculus simulation, revealing the instability mechanism of the surrounding rock of the roadway under the stress disturbance environment, and when not affected by the adoption, the roadway forms a certain stress concentration area within the effective range of support. During mining, under the comprehensive action of the original peripheral stress field and the mining stress field, the cliffhanger is unstable under the comprehensive action of the original peripheral stress field and the mining stress field, and the extrusion and stretching effect of the unflapped part of the rock layer above the goaf section of the coal seam is set up along the air, resulting in violent deformation such as the bottom drum, and the rotational sinking of this part of the unflinted rock layer further aggravates the transfer of the overburden load to the surrounding rock of the lane, so that the surrounding rock along the empty lane is subjected to a large additional stress, and the mining stress field plays a leading role, and the mining stress "far field" is the compound stress field, of which the tensile stress is the leading destructive factor. The deformation of the surrounding rock is mainly based on the bottom, and the horizontal stress on the bottom plate along the empty lane is mainly generated by the horizontal strain that occurs after the lower rock layer of the filling body and the coal gang is subjected to the supporting pressure transmitted by the top plate. With the mining of the working surface, the roof of the goaf area is broken and collapsed to form the characteristics of "vertical three belts, " which is affected by the "large support" of the coal body of the working surface and the "small support" of the surrounding rock along the empty roadway, and the pressure relief of the cut roof can make the roof plate along the empty lane change from the "long arm beam" structure when the roof is not cut into the "short arm beam" structure, blocking the lateral stress of the goaf area to the roof plate of the alley and significantly reducing the degree of stress superposition of the roof plate of the alley. The technical means of blasting cutting roof active pressure relief and protective lane are used to block the transmission of lateral support pressure, the roof slate layer is precracked in advance, the sinking of the rock layer is accelerated, the disturbance time is reduced, the vertical stress of the rock layer and the rock layer above it along the empty roadway is reduced, the vertical stress concentration of the roadway is reduced, the stress concentration coefficient is reduced, the degree of damage of the surrounding rock after the top is weakened, the damage range is reduced, and the technical problem of large deformation prevention and control along the bottom drum of the empty alley can be solved. Constructing the mechanical structure model of the top plate of the cut top pressure relief and the uncut top pressure relief along the empty lane, the stress change characteristics of the active protective rock surrounding rock along the hollow top of the cut top pressure relief were calculated, and after the technical scheme of the blasting cut top active pressure relief and protection lane was adopted, the deformation along the empty roadway was significantly weakened, the stability of the surrounding rock of the roadway after the blasting of the cut roof was significantly improved, the maintenance state along the section of the empty roadway was good, and the cross-sectional convergence rate was reduced by 37.3% compared with the original section. Cutting the roof active pressure relief and protective lane can effectively improve the stability of the surrounding rock.